MATHEMATICAL MODELS OF FUNCTIONING OF THE ENTERPRISES PARTICIPATING IN THE INNOVATION ACTIVITY - Inna Viktorovna Lebedeva; Victor Ivanovich Lebedev (Вестник Северо-Кавказского федерального университета, 2022)
Developing economic enterprise models with innovations in the manner of systems of the nonlinear differential equations are studied. Regular and stochastic behaviors of the economic systems are considered. Optimum ways of development management of enterprises with innovations are discussed.